The effectiveness of a proposed cognitive-behavioral treatment program to reduce depression among mothers of children with congenital anomalies - Al-Saud, Asma Mahmoud (Journal of Educational and Psychological Sciences, 2022)
The study aims to identify the effectiveness of the cognitive behavioral therapy in decreasing the depression of the mothers of the children who have birth defects and registered in the Future Palestine Association in the Gaza strip, in addition to know the extent of the continuing of this effectiveness after the follow- up period for one month after the end of the application of the therapeutic sessions. The sample of the study consists of (30) of the mothers of the children who have birth defects and registered in the Future Palestine Association in the Gaza strip. The sample is divided into two groups, the first one is the experimental group which consists of 15 mothers and the second is the control group which also consists of 15 mothers. The sample is selected from the children mothers' who are registered in the Future Palestine Association and they are selected in an intentional way. The study used the following measures to examine the hypotheses of the study: Beck depression measure, the proposed program which prepared by the researcher and the special forms of the cognitive- behavioral therapy. The study used the experimental method by using two equivalent groups which are the cognitive behavioral therapy The study found the following results: There are statistical significant differences in the depression level between the experimental group and the control group in the medium measure during the application of the behavioral cognitive therapy program. There are statistical significant differences in the depression level between the experimental group and the control group in the post measure. There are statistical significant differences in the depression level of the experimental group in the medium and pre measures. There are statistical significant differences in the depression level of the experimental group in the pre and the post measures. There are no statistical significant differences in the depression level of the experimental group in the post and the iterative measures، Among the most important recommendations of the study: encouraging mothers and fathers to participate in counseling programs and to receive the necessary rehabilitation services for their children, given the positive impact of those programs on them and their children.
Keywords: the cognitive behavioral therapy; depression; the mothers of the children- birth defects; birth defects